IMPLEMENTASI QUANTUM LEARNING BERBANTUAN QR PADA PEMBELAJARAN IPAS SISWA KELAS 6 - Qurnia Permata; Puspita, Ryan Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the results of Science Learning Outcomes Using the QR-Assisted Quantum Learning Method. This study uses the Quantum Learning Method. The subjects of this study were grade VI students of SD IT Maryam Muraith in the even semester of the 2024/2025 academic year consisting of 14 students. This study uses a classroom action approach (CAR) consisting of two cycles, each cycle includes the planning, implementation, observation, and reflection stages. The instruments used include observation sheets, learning outcome tests, and documentation. The results of the study show that the application of QR-assisted Quantum Learning can significantly improve student learning outcomes. In cycle I, the average student score increased from the low category to the medium category, and in cycle II there was a further increase to reach the high category. This increase occurred because the Quantum Learning method supported by QR media was able to create an interactive learning atmosphere, trigger curiosity, and increase student involvement in the learning process. Thus, the application of this method is recommended as an alternative effective Science learning strategy at the elementary school level.